Lamb production and consumption dynamic in Mexico from 1970 to 2019 - Bobadilla-Soto, Encarnación Ernesto (2021)
Introduction. The volume of lamb meat production in Mexico did not satisfy the demand, mainly for the preparation of the traditional dish ‘barbacoa’. Objective. To evaluate the dynamics of lamp meat production and consumption in Mexico. Materials and methods. The statistical information was obtained from Mexico’s official publications from 1970 to 2019. Increases/decreases, the annual growth rate and the seasonal index calculated with the method of average percentages, were determined, the last one was calculated by the average percentage method. The data per month was shown as cost and production percentages. Results. The sheep carcass meat production from 1970 to 2019 had an average annual growth rate of 2,2 %, in 2019 production was 64,030 tons; sheep meat paid better (USD per kg) compared to other livestock species. In 2019 the prices paid were 1.47, 1.69, 1.54, 1.34, and 1.08 for sheep (Ovis aries), cattle (Bos taurus), goats (Capra hircus), pigs (Sus scrofa) and chickens (Gallus gallus domesticus), respectively. The seasonality index for live sheep production showed that from January to May were when there was the lowest production (<100), and from June to December the highest (>100). The variability of the seasonality index of sheep meat prices were from 99.1 up to 100.7 %, for this index the variation was very low (1.6 %), this meant a stable price all year round; the per capita consumption in Mexico went from 467 to 567 g from 1970 to 2019. Conclusion. There was a strong seasonality in production; however, the price remained constant throughout the year, due to the fact that imports stabilized the price in the low production season in Mexico.